Sistema de control y monitoreo en las áreas de producción agrícola de la Espam MFL - Mendoza Vera, Gema Teresa (2015)
In order to maintain effective information record production areas of the School of Agricultural System Monitoring and Control was created. For the effect was of vital importance to an analysis methods of recording and reporting information used by administrators. Using information obtained from interviews it was found that these had few resources to enable it to optimize the management of it, so the implementation of a beneficiary them greatly. To prepare the system and show that the results are supported technically worked with the development methodology MIDAS, it consists of four phases, in which the gathering of requirements was performed to define the requirements and architecture of the web application designing a prototype of it to provide the customer with a first version of the product. Continuing the development of database and programming interfaces, which were developed in Microsoft SQL Server 2008 and the integrated development environment for Microsoft Visual Studio C # language and object-oriented programming and thus verify proper operation the control and monitoring system for subsequent implementation, development finalizing the testing phase, which allowed demonstrate the reduction of 92,98% in the time data entry and report generation.